Delayed acute myocarditis and COVID‐19‐related multisystem inflammatory syndrome. (26th October 2020) - Nicol, Martin; Cacoub, Lea; Baudet, Mathilde; Nahmani, Yoram; Cacoub, Patrice; Cohen‐Solal, Alain; Henry, Patrick; Adle‐Biassette, Homa; Logeart, Damien
Abstract: Precise descriptions of coronavirus disease 2019 (COVID‐19)‐related cardiac damage as well as underlying mechanisms are scarce. We describe clinical presentation and diagnostic workup of acute myocarditis in a patient who had developed COVID‐19 syndrome 1 month earlier. A healthy 40‐year‐old man suffered from typical COVID‐19 symptoms. Four weeks later, he was admitted because of fever and tonsillitis. Blood tests showed major inflammation. Thoracic computed tomography was normal, and RT–PCR for SARS‐CoV‐2 on nasopharyngeal swab was negative. Because of haemodynamic worsening with both an increase in cardiac troponin and B‐type natriuretic peptide levels and normal electrocardiogram, acute myocarditis was suspected. Cardiac echographic examination showed left ventricular ejection fraction at 45%. Exhaustive diagnostic workup included RT–PCR and serologies for infectious agents and autoimmune blood tests as well as cardiac magnetic resonance imaging and endomyocardial biopsies. Cardiac magnetic resonance with T2 mapping sequences showed evidence of myocardial inflammation and focal lateral subepicardial late gadolinium enhancement. Pathological analysis exhibited interstitial oedema, small foci of necrosis, and infiltrates composed of plasmocytes, T‐lymphocytes, and mainly CD163 + macrophages. These findings led to the diagnosis of acute lympho‐plasmo‐histiocytic myocarditis. There was no evidence of viral RNA within myocardium. The only positive viral serology was for SARS‐CoV‐2. The patient and his cardiac function recovered in the next few days without use of anti‐inflammatory or antiviral drugs. This case highlights that systemic inflammation associated with acute myocarditis can be delayed up to 1 month after initial SARS‐CoV‐2 infection and can be resolved spontaneously.